Understanding of BRCA1/2 genetic tests results: the importance of objective and subjective numeracy. Issue 10 (14th April 2014) - Hanoch, Yaniv; Miron‐Shatz, Talya; Rolison, Jonathan J; Ozanne, Elissa
Abstract Background The majority of women (71%) who undergo BRCA1/2 testing—designed to identify genetic mutations associated with increased risk of cancer—receive results that are termed 'ambiguous' or 'uninformative negative'. How women interpret these results and the association with numerical ability was examined. Methods In this study, 477 women at increased risk for breast and ovarian cancer were recruited via the Cancer Genetics Network. They were presented with information about the four different possible BRCA1/2 test results—positive, true negative, ambiguous and uninformative negative—and asked to indicate which of six options represents the best response. Participants were then asked which treatment options they thought a woman receiving the results should discuss with her doctor. Finally, participants completed measures of objective and subjective numeracy. Results Almost all of the participants correctly interpreted the positive and negative BRCA1/2 genetic test results. However, they encountered difficulties interpreting the uninformative and ambiguous BRCA1/2 genetic test results. Participants were almost equally likely to think either that the woman had learned nothing from the test result or that she was as likely to develop cancer as the average woman. Highly numerate participants were more likely to correctly interpret inconclusive test results (ambiguous, OR = 1.62; 95% CI [1.28, 2.07]; p < 0.001; uninformative, OR = 1.40; 95% CI [1.10, 1.80]). Discussion Given the medical and psychological ramifications of genetic testing, healthcare professionals should consider devoting extra effort to ensuring proper comprehension of ambiguous and uninformative negative test results by women. Copyright © 2014 John Wiley & Sons, Ltd.